Joyce the Deconstructionist: Finnegans Wake in Context - J., Zangouei (k@ta: A Biannual Publication on the Study of Language and Literature, 2012)
Had Finnegans Wake not been written, some seminal post-1950s innovations in the field of modern literary theory and criticism would have been impossible. James Joyce, who seems to have inspiringly influenced the entire sphere of modern literary theory and criticism greatly, is a pioneer of deconstruction too. His last novel, which reflects his deconstructive tendencies, has played a seminal role in the formation of 20th century deconstruction, and comprises an inchoate mass of implicit ideas on the subject. It was perhaps not until Jacques Derrida and his deconstruction techniques that the theory implied by Finnegans Wake really came into focus. This article seeks to delineate Derrida’s theory of deconstruction as well as Joyce's deconstructive aesthetics; and taking a diachronic approach to literary theory and criticism it glances at Finnegans Wake in the light of deconstruction.